Principles of Information Systems : A Managerial Approach - Stair, Ralph M. (Australia Thomson Course Technology, 2008)
A text that covers topics of information technology. It helps students to understand and practice fundamental IS principles
Include Index
Keywords: Management information systems -- Information technology--Management -- Australasia